Follicle profile and plasma gonadotropin concentration in pubertal female ponies - Nogueira, Guilherme de Paula [UNESP] (Associação Brasileira de Divulgação Científica (ABRADIC), 2004)
Twelve female ponies were examined daily for 30 days and classified as ovulating (OV; N = 6; 197 ± 6 kg) or prepubertal (PP; N = 6; 196 ± 9 kg). Follicles were detected by ultrasound and gonadotropins quantified by radioimmunoassay. The mean diameter of the largest follicles was significantly larger in OV (38 ± 1 mm) than in PP (26 ± 2 mm) but there was no difference between groups in the size of the second largest follicle. There were more small follicles (<24 mm) in the PP than in the OV group, but PP fillies had a smaller number of follicles >29 mm than the OV fillies. Follicle-stimulating hormone (FSH) levels did not differ between groups but PP fillies had lower luteinizing hormone (LH) peak (8 ± 1 ng/ml) and basal (4 ± 0.5 ng/ml) levels, lower peak magnitude (2 ± 0.2 ng/ml) and period average (5 ± 0.6 ng/ml) than OV fillies (32 ± 4.5, 8 ± 1.2, 17.1 ± 6, and 15 ± 2.3 ng/ml, respectively). The PP group, in contrast to the OV group, showed no relationship between FSH surge and follicle wave emergence. We conclude that an LH concentration higher than 8 ng/ml is needed for follicle growth to a preovulatory size. Wave emergence and FSH secretion seem to be independent events, probably due to an inhibitory neural system in these PP animals. PP fillies may provide a physiological model for the study of follicle wave emergence which apparently does not depend on gonadotropin levels.
Keywords: Follicles; FSH; LH and prepubertal fillies